Role of Proteases in Chronic Obstructive Pulmonary Disease - Pandey, Kailash C.; De, Sajal; Mishra, Pradyumna K. (Frontiers in Pharmacology, 2017)
Chronic obstructive pulmonary disease (COPD) is generally associated with progressive destruction of airways and lung parenchyma. Various factors play an important role in the development and progression of COPD, like imbalance of proteases, environmental and genetic factors and oxidative stress. This review is specifically focused on the role of proteases and their imbalance in COPD. There are three classes (serine, mettalo and cysteine) of proteases involved in COPD. In serine proteases, neutrophil elastase, cathepsin G and proteinase-3 are involved in destruction of alveolar tissue. Matrix-mettaloproteases-9, 12, 13, plays an influential role in severity of COPD. Among cysteine proteases, caspase-3, caspases-8 and caspase-9 play an important role in controlling apoptosis. These proteases activities can be regulated by inhibitors like α-1-antitrypsin, neutrophil elastase inhibitor and leukocyte protease inhibitor. Studies suggest that neutrophil elastase may be a therapeutic target for COPD, and specific inhibitor against this enzyme has potential role to control the disease. Current study suggests that Dipeptidyl Peptidase IV is a potential marker for COPD. Since the expression of proteases and its inhibitors play an important role in COPD pathogenesis, therefore, it is worth investigating the role of proteases and their regulation. Understanding the biochemical basis of COPD pathogenesis using advanced tools in protease biochemistry and aiming towards translational research from bench-to-bedside will have great impact to deal with this health problem